The establishment and role of HOPE Cape Town in the fighting of HIV and AIDS in Cape Town, South Africa : a case study - Louw, Edwin Leonard (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.